Effects of Biochar With Inorganic and Organic Fertilizers on Agronomic Traits and Nutrient Absorption of Soybean and Fertility and Microbes in Purple Soil - Liu, Ming; Linna, Cholidah; Ma, Shumin; Ma, Qun; Guo, Jinge; Wang, Fenfen; Wang, Longchang (Frontiers in Plant Science, 2022)
Biochar is a kind of organic matter that can be added into the soil as a soil amendment to improve its quality. What are the effects of using biochar on purple soil and soybeans? Can the use of biochar reduce the use of fertilizers? This is our concern. Therefore, we carried out this study. The objectives of our study were to evaluate the effects of biochar, inorganic and organic fertilizer application on plant growth, chlorophyll content, photosynthetic gas exchange, and yield of soybean as well as fertility and microbial community in purple soil, and to appraise the possible reduction rate of inorganic fertilizer under the biochar application. A pot experiment was conducted with three levels of biochar, two levels of inorganic fertilizer, and two levels of organic fertilizer in a randomized complete block. The results indicated that the low rate of biochar together with half rate of inorganic fertilizer and organic fertilizer increased the plant growth of soybean. Meanwhile, the chlorophyll content, root growth, and yield of soybean were increased by 16.61, 197.73, and 96.7%, respectively, with biochar compared with no biochar. The high rate of biochar with half rate of inorganic fertilizer and organic fertilizer can promote the exchange of photosynthetic gas in soybean, and the photosynthetic rate increased by 45.25% compared with the blank control. At the full pod stage, the nitrogen content, phosphorus content, and potassium content of the whole plant under the high rate of biochar were 28.35, 13.65, and 28.78%, respectively, higher than that of the blank control. The application of biochar increased nitrogen, phosphorus, and potassium uptake of soybean. The high rate of biochar with half rate of inorganic fertilizer and organic fertilizer can improve soil nutrient content and soil microbial community. Compared with no biochar treatments, total organic carbon (TOC) increased by 740.28%, and cation exchange capacity (CEC) increased by 54.17%. Phospholipid fatty acid (PLFA) increased by 65.22%, and all kinds of soil microorganisms increased to varying degrees. In conclusion, the application of biochar can reduce the use of organic and inorganic fertilizers, improve the agronomic traits and yield of soybean, and play a positive role in soil nutrients and soil microorganisms.